Adult pilocytic astrocytomas: clinical features and molecular analysis. Issue 6 (26th January 2014) - Theeler, Brett J.; Ellezam, Benjamin; Sadighi, Zsila S.; Mehta, Vidya; Tran, M. Diep; Adesina, Adekunle M.; Bruner, Janet M.; Puduvalli, Vinay K.
Abstract: Background: Adult pilocytic astrocytomas (PAs) are rare and have an aggressive clinical course compared with pediatric patients. Constitutive Ras/RAF/MAPK signaling appears to be an important oncogenic event in sporadic PA. We evaluated clinical data and molecular profiles of adult PAs at our institution. Methods: We identified 127 adult PAs in our institutional database. Cases with available tissue were tested for BRAF-KIAA1549 fusion/duplication (B-K fusion) by fluorescence in situ hybridization and submitted for mutation profiling using the Sequenom mutation profiling panel. Subgroup analyses were performed based on clinical and molecular data. Results: The majority of adult PAs are supratentorial. Twenty-two percent of cases had an initial pathologic diagnosis discordant with the diagnosis made at our institution. Recurrence was seen in 42% of cases, and 13% of patients died during follow-up. Adjuvant radiotherapy following surgical resection was associated with a statistically significant decrease in progression-free survival ( P = .004). B-K fusion was identified in 20% (9 of 45) of patients but was not associated with outcome. No BRAF V600E mutations (0 of 40 tested) were found. Conclusion: This was the largest single institution series of adult PA. A significant proportion of adult PAs follow an aggressive clinical course. Our results support a period of observation following biopsy or surgical resection. B-K fusion in adult PA does not influence outcome, and BRAF V600E mutation appears to be a very rare event. Further study of tumor biology and optimal treatment is needed, given a more aggressive clinical behavior.